(NsEMEN pROKOFXEWI^ wLASOW (B:s (NhIMIK(B-(NSAMOU^KA(B, 1789-1821 /s - (NhOLODILIN(B, (NnIKOLAJ nIKOLAEWI^s; (NhOLODILIN(B, (NaLEKSANDR nIKOLAEWI^s; (NrASKIN(B, (Nn(B.(Nm(B.s ((Nl(B. :s (NnAUKA(B. (NlENINGR(B. (NOTD(B-(NNIE(B,s, 1988)
(NsO^(B. (Ns(B.(Np(B. (NwLASOWA(B, (NST(B. (NO NEM (B: (NS(B. 123-127 (82 (NNAZW(B.)s
(NiMEN(B. (NUKAZ(B.: (NS(B. 128-133s
(Nan sssrs
Keywords: (NwLASOW(B, (NsEMEN pROKOFXEWI^s; (NhIMI^ESKAQ NAUKA W rOSSII (B- (NiSTORIQ (B- 18-19 (NWW(B.s